1983
DOI: 10.1111/j.1365-2761.1983.tb00073.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Herpes virus vitreum isolated from hyperplastic epidermal tissue of walleye, Stizostedion vitreum vitreum (Mitchill)*

Abstract: A new virus, provisionally named Herpesvirus vitreum, was isolated from hyperplastic epidermal tissue from a walleye, Stizostedion vitreum vitreum (Mitchill), taken in Saskatchewan, Canada. The virus, which was isolated in the walleye ovarian (WO) cell line, was identified as a herpesvirus on the basis of size (190-230 nm), morphology and apparent pattern of replication. The virus, which passes polycarbonate membranes of 200 nm mean pore diameter, was ether-labile. Virus replicated in WC-1 cells at 4 and 15X, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

1985
1985
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(26 citation statements)
references
References 23 publications
(15 reference statements)
1
25
0
Order By: Relevance
“…The tumors are lymphocystis and dermal sarcoma described earlier (YAMAMOTO et al, 1976) and two types of epidermal hyperplasias-one de scribed as a diffuse form and the other described as a discrete form. The analysis of thin-sections re vealed the association of a lymphocystis virus and a retrovirus (YAMAMOTO et al, 1976); a herpesvirus (KELLY et al, 1980(KELLY et al, , 1983, and a different retro virus (unpublished observation) for the respective tumors. The physical appearance, histological na ture and electron microscopic observations are described.…”
Section: Methodsmentioning
confidence: 88%
See 2 more Smart Citations
“…The tumors are lymphocystis and dermal sarcoma described earlier (YAMAMOTO et al, 1976) and two types of epidermal hyperplasias-one de scribed as a diffuse form and the other described as a discrete form. The analysis of thin-sections re vealed the association of a lymphocystis virus and a retrovirus (YAMAMOTO et al, 1976); a herpesvirus (KELLY et al, 1980(KELLY et al, , 1983, and a different retro virus (unpublished observation) for the respective tumors. The physical appearance, histological na ture and electron microscopic observations are described.…”
Section: Methodsmentioning
confidence: 88%
“…A summary of the four different growths on the skin of walleye together with their associated viruses is summarized in Table 2. The initial virus propagation in cell culture from an epidermal hyperplasia was a herpesvirus (KELLY et al, 1980(KELLY et al, , 1983. However electron microscopic analysis showed that another epidermal hyper plasia-the discrete form was more common.…”
Section: Propagation Of Walleye Dermal Virusesmentioning
confidence: 99%
See 1 more Smart Citation
“…Temperature-dependent replication of herpesviruses of fish has been observed. Herpesvirus vitrieum from hyperplastic epidermal tissue of walleye Stizostedion vitreum vitreum replicated at 4 and 15 "C but not at 20 " C , a temperature most suitable for walleye ovary (WO) cell growth (Kelly et al 1983).…”
Section: O Inter-research 1992mentioning
confidence: 99%
“…These viruses include channel catfish virus (CCV) (Wolf and Darlington, 1971), Herpesvirus sal monis (Wolf et al, 1978), NeVTA (nerka virus of Towada Lake, Akita and Aomori) (Sano, 1976), Oncorhynchus masou virus (OMV) (Kimura et al, 1981), yamame tumor virus (Sano et al, 1983), Herpesvirus vitreum (walleye herpesvirus) (Kelly et al, 1983), Herpesvirus cyprini (Sano et al, 1985) and Herpesvirus anguillae (Sano et al, 1990). Among these viruses, CCV, NeVTA, YTV, OMV and CHV were experi mentally demonstrated to be able to produce high mortality rate among inoculated fish.…”
mentioning
confidence: 99%